LUKIS TONG SAMPAH SEBAGAI UPAYA PENANAMAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA ANAK USIA DINI - Achmad syafi'i (Abdi Seni, 2019)
AbstractÂ Efforts to plant Clean and Healthy Behavior (PHBS) need to be instilled in children from an early age. Trash painting training aims to foster Clean and Healthy Behavior (PHBS) because seeing existing trash cans tends to be dull and less attractive to children. The purpose of painting a trash can, which is to make children interested in throwing trash in its place, a moral message that is easily understood through the pictures depicted, and able to make the trash can product as a place of entrepreneurship. The activity carried out involved 90 students, consisting of all students of Large and Small Kindergarten. Implementation techniques use â€œbrainstormingâ€ and persuasive methods. Through these two methods children can be encouraged to bring up their ideas and imagination. With that in mind, the studentsâ€™ creativity is honed and developed well, as evidenced by the results of painting on trash cans that are colorful and contain certain moral messages.Keywords: Clean and Healthy Life Behavior, Early Age, Painting, Trash.